Effects of Scanning Strategies, Part Orientation, and Hatching Distance on the Porosity and Hardness of AlSi10Mg Parts Produced by Laser Powder Bed Fusion - Naol Dessalegn Dejene; Wakshum Mekonnen Tucho; Hirpa G. Lemu (Journal of Manufacturing and Materials Processing)
Laser powder bed fusion (L-PBF) shows potential in metal additive manufacturing for producing complex components. However, achieving ideal hardness and minimizing porosity poses a significant challenge. This study explores the impact of part orientation, scanning methods, and hatching distance on the hardness and porosity of AlSi10Mg alloy produced through L-PBF. Utilizing a Box–Behnken design of experiments (DOE), cubic samples were systematically produced. Hardness was quantitatively assessed using Vickers hardness tests, while porosity measurements involved 2D image analysis of polished scanning electron microscopy (SEM) samples, the porosity percentages analyzed using ImageJ software. The results demonstrate that both scanning strategy and hatching distance significantly influence hardness and porosity. The spiral scanning pattern notably enhances hardness and reduces porosity. In contrast, the bidirectional scanning strategy results in lower hardness and more pronounced porosity formations. An inverse correlation between grain size distribution and hardness was observed, with finer grain sizes leading to higher hardness values, indicating that grain refinement improves mechanical properties. Additionally, a negative relationship between hardness and porosity was established, emphasizing the importance of minimizing porosity to enhance material hardness. These findings contribute to the overall understanding of the L-PBF additive manufacturing process, providing valuable insights for optimizing material properties and ensuring the mechanical integrity of high-performance L-PBF produced metal parts.